Rampant Misexpression in a Mimulus (Monkeyflower) Introgression Line Caused by Hybrid Sterility, Not Regulatory Divergence. (20th March 2020) - Kerwin, Rachel E; Sweigart, Andrea L
Abstract: Divergence in gene expression regulation is common between closely related species and may give rise to incompatibilities in their hybrid progeny. In this study, we investigated the relationship between regulatory evolution within species and reproductive isolation between species. We focused on a well-studied case of hybrid sterility between two closely related yellow monkeyflower species, Mimulus guttatus and Mimulus nasutus, that is caused by two epistatic loci, hybrid male sterility 1 ( hms1 ) and hybrid male sterility 2 ( hms2 ). We compared genome-wide transcript abundance across male and female reproductive tissues (i.e., stamens and carpels) from four genotypes: M. guttatus, M. nasutus, and sterile and fertile progeny from an advanced M. nasutus – M. guttatus introgression line carrying the hms1–hms2 incompatibility. We observed substantial variation in transcript abundance between M. guttatus and M. nasutus, including distinct but overlapping patterns of tissue-biased expression, providing evidence for regulatory divergence between these species. We also found rampant genome-wide misexpression, but only in the affected tissues (i.e., stamens) of sterile introgression hybrids carrying incompatible alleles at hms1 and hms2 . Examining patterns of allele-specific expression in sterile and fertile introgression hybrids, we found evidence for interspecific divergence in cis- and trans- regulation, including compensatory cis–trans mutations likely to be driven by stabilizing selection. Nevertheless, species divergence in gene regulatory networks cannot explain the vast majority of the gene misexpression we observe in Mimulus introgression hybrids, which instead likely manifests as a downstream consequence of sterility itself.